Genetic basis and principal component analysis in cotton (Gossypium hirsutum L.) grown under water deficit condition - Ullah, Aziz; Shakeel, Amir; Ahmed, Hafiz Ghulam Muhu-Din; Naeem, Muhammad; Ali, Muhammad; Shah, Adnan Noor; Wang, Lichen; Jaremko, Mariusz; Abdelsalam, Nader R.; Ghareeb, Rehab Y.; Hasan, Mohamed E. (Frontiers in Plant Science, 2022)
ABSTRACT The shortage of irrigation water is a major constraint to cotton productivity. This research was carried out to study the genetic basis of variation for water deficit tolerance in cotton. For this purpose, 40 diverse genotypes of upland cotton were screened under normal and water deficit condition in research area of Department of Plant Breeding and Genetics, UAF. This experiment was conducted in split plot design under RCBD arrangement. All the genotypes showed significant difference under two moisture levels. The interaction of cotton genotypes with two moisture levels were studied for seed cotton yield and stress susceptibility index. For the development of genetic material, 10 drought tolerant and 5 drought sensitive genotypes were crossed in line × tester mating design. For the evaluation of genetic material, 50 F1 crosses and their 15 parents was field planted under two moisture regimes i.e. normal and water deficit condition. For most of yield related traits VH-144, VH-295, CIM-443 and FH-1000 showed good general combining ability under water deficit condition. For most of yield related traits the best cross combinations were VH-144 × S-12, NIAB-111 × IR-3 and VH-295 × MNH-147 under drought condition. All yield related traits having non-additive gene action suggested usage of this material in cotton hybrid development programme for drought hit areas of Pakistan.